Mitigation of tremor in hands using an active mass damper - TADA, Kaoru; KOMATSUZAKI, Toshihiko; MATSUDA, Masashi; HATANAKA, Satoshi (Kikai Gakkai ronbunshū = Transactions of the Japan Society of Mechanical Engineers, 2019)
In this study, we devised an active device which is used to suppress the essential tremor in human limb. The tremor can be observed in most human arms under excessive stress or chills, even he/she is at physically well condition. Therefore, the tremor may cause anyone a bad effect on precise operation, e.g. welding and surgery. In this work, experiments are performed where the simulated microscopic surgery is imposed on subjects whose fingers are equipped with the active mass damper attenuating the tremor in their hands. The damper is actively driven according to the state feedback controller designed according to the linear two-degrees-of-freedom vibration system model. Subjects were asked to grip a needle having a relatively small diameter using tweezers, and were also asked to insert it in a needle with a larger diameter. Tremors were measured while the subjects kept the tip of the needle in place. The damper was shown to be effective for attenuating vibration in human fingers.